Polymers from renewable resources. Biodegradable polymers - Penczek, S.; Pretula, J.; Lewiński, P. (Polimery, 2013)
This paper is an extended version of the presentation at the opening session of the Seminar (BIOGRATEX Project) at the Lodz University of Technology, the Department of Material and Commodity Sciences and Textile Metrology, chaired by Professor Izabella Krucińska. It is not intention of this paper to give an extensive coverage of the subject indicated in the title. Instead, it wishes to present this subject to the more general audience and to show the research opportunities in Poland. Besides, the differences existing in the terminology and nomenclature in the area of biobased/biodegradable polymers are discussed in detail. The prospect of running out of traditional fossil raw materials is shown and the potential use of the materials from renewable resources for synthesis of polymers is presented.